2016
DOI: 10.1038/ncomms13162
|View full text |Cite
|
Sign up to set email alerts
|

Absolute abundance of southern bluefin tuna estimated by close-kin mark-recapture

Abstract: Southern bluefin tuna is a highly valuable, severely depleted species, whose abundance and productivity have been difficult to assess with conventional fishery data. Here we use large-scale genotyping to look for parent–offspring pairs among 14,000 tissue samples of juvenile and adult tuna collected from the fisheries, finding 45 pairs in total. Using a modified mark-recapture framework where ‘recaptures' are kin rather than individuals, we can estimate adult abundance and other demographic parameters such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
155
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(176 citation statements)
references
References 38 publications
2
155
0
2
Order By: Relevance
“…If however such large samples are collected, other population quantities can be estimated using the same data. Absolute abundance and demographic parameters (fecundity, mortality) can be estimated with the close‐kin mark–recapture (CKMR) method (Bravington, Grewe, & Davies, ; Bravington, Skaug, & Anderson, ). This method is based on the identification of pairs of close relatives (parents–offspring or half sibling pairs).…”
Section: Resultsmentioning
confidence: 99%
“…If however such large samples are collected, other population quantities can be estimated using the same data. Absolute abundance and demographic parameters (fecundity, mortality) can be estimated with the close‐kin mark–recapture (CKMR) method (Bravington, Grewe, & Davies, ; Bravington, Skaug, & Anderson, ). This method is based on the identification of pairs of close relatives (parents–offspring or half sibling pairs).…”
Section: Resultsmentioning
confidence: 99%
“…If such an explanation were supported, a large‐scale genetic sibship or parent‐offspring‐based tagging studies could allow managers to identify sea lamprey natal stream origins, which is the highest priority for the Great Lakes Sea Lamprey Control Program (SLCB Research Priorities, ). The feasibility and efficacy of genetic tagging studies to provide valuable management insights have been demonstrated across a broad range of species (Anderson & Garza, ; Bravington, Grewe, & Davies, ; De Barba et al, ). Importantly, genetic tagging studies can confidently identify full‐ and half‐sibling relationships without genotyping parents (Jones & Wang, ), especially when several hundred loci are genotyped (Santure et al, ) as demonstrated by simulated and empirical data shown here.…”
Section: Discussionmentioning
confidence: 99%
“…These preliminary results are based on only two tributaries but suggest an intriguing explanation that the genetic similarities of larvae TA B L E 4 Summary statistics from pedigree analyses for larval sea lamprey of different age classes collected from two streams management insights have been demonstrated across a broad range of species (Anderson & Garza, 2006;Bravington, Grewe, & Davies, 2016;De Barba et al, 2010). Importantly, genetic tagging studies can confidently identify full-and half-sibling relationships without genotyping parents (Jones & Wang, 2010), especially when several hundred loci are genotyped (Santure et al, 2010) as demonstrated by simulated and empirical data shown here.…”
Section: Effects Of Outlier Loci On Spatial Population Structurementioning
confidence: 97%
“…Bravington, Grewe, et al () took the viewpoint that offspring tag their parents, while here we have reversed the direction of tagging. This may appear arbitrary, but Skaug () pointed out that the direction of tagging (called the offspring–centric vs. parent–centric perspectives by him) can affect the complexity of the statistical derivations.…”
Section: Discussionmentioning
confidence: 99%